An itchy rash and muscle weakness. Issue 9 (30th August 2021) - Risavi, Brian L.; Puller, Justin; Juhasz, Kristin
Abstract: Dermatomyositis is a rare disease affecting primarily skin and muscles and is associated with malignancies, especially in at‐risk patients. Clinical presentations vary widely but proximal muscle weakness and typical skin findings should prompt consideration of the diagnosis. Immunosuppressive therapy is required, as is continued screening for malignant disease during follow‐up. Abstract : Dermatomyositis is a rare disease affecting primarily skin and muscles and is associated with malignancies, especially in at‐risk patients. Clinical presentations vary widely but proximal muscle weakness and typical skin findings should prompt consideration of the diagnosis. Immunosuppressive therapy is required, as is continued screening for malignant disease during follow‐up.